2023
DOI: 10.1002/app.55034
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight, robust, porous heterocyclic para‐aramid aerogel hollow fibers for multifunctional applications

Wenwen Wu,
Qingquan Song,
Na Li
et al.

Abstract: In nature, many fibers with warmth‐retention properties, such as the hair of polar bears and rabbits, both have a hollow cross‐section structure. The static air in fiber cavities can effectively inhibit heat conduction and serve as an effective thermal insulator. In this work, the high‐performance heterocyclic para‐aramid polymer was selected as the spinning solution, and aerogel hollow fiber was prepared by coaxial wet spinning and freeze‐drying techniques. The effects of spinning solution concentration and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Through analysis, it was found that ANFs were nested in the aerogel matrix as a supporting skeleton, laying the foundation for mechanical properties. Besides, Wang, Ma, and Wu also added ANFs to the aerogels to overcome the brittleness of aerogels. Therefore, aramid nanofibers, with incomparable mechanical properties, have become a star material as reinforcement for robust and elastic composite aerogels. , …”
Section: Introductionmentioning
confidence: 99%
“…Through analysis, it was found that ANFs were nested in the aerogel matrix as a supporting skeleton, laying the foundation for mechanical properties. Besides, Wang, Ma, and Wu also added ANFs to the aerogels to overcome the brittleness of aerogels. Therefore, aramid nanofibers, with incomparable mechanical properties, have become a star material as reinforcement for robust and elastic composite aerogels. , …”
Section: Introductionmentioning
confidence: 99%